The fields of cultural criticism in the poetry of contradictions from the textual structure to the social structure - نصّور, أزدشير; عدنان محمّد أحمد, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The texts of contradictions are subjected to the mechanisms of cultural study as discourses that transcend aesthetic, elitist, and institutional boundaries, so that the text becomes a mirror of the ideological problems that may befall society. Therefore, it is necessary to dismantle the partial structures within the text and reconstruct them culturally and socially in order to reach the semantics of public discourse, the truth hidden behind the mask of rhetoric and its textual data such as exaggerations, antagonistic dichotomies, repetition, and other things that may include systems affecting the Umayyad social structure. Since the "poet" artist is a social actor, his act "art" will necessarily be affected by the data of the social structure. Here, his work must be read in accordance with the "aesthetic" textual structure and the social and historical construction referring to the "cultural".Or rather, we must start from the textual structure and its related components in order to reach the constituent connotations of the general social structure; That is, the transition from what is individual to what is collective, with the necessity of art, which requires that creative work do not remain confined to itself or its product.